2006
DOI: 10.1111/j.1524-4725.2006.32283.x
|View full text |Cite
|
Sign up to set email alerts
|

Photorejuvenation by Intense Pulsed Light with Objective Measurement of Skin Color in Japanese Patients

Abstract: IPL skin rejuvenation using relatively shorter wavelengths and pulse widths brought about significant macroscopic and quantitative improvements, especially in the treatment of epidermal pigmentation and improvement of basic skin tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…8,10 Fibroblasts, the major cellular components in skin dermis, are the key cells responsible for the biosynthesis of extracellular matrix (ECM) proteins. 11 The effects of IPL on skin fibroblast activity remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,10 Fibroblasts, the major cellular components in skin dermis, are the key cells responsible for the biosynthesis of extracellular matrix (ECM) proteins. 11 The effects of IPL on skin fibroblast activity remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Rough endoplasmic reticula, polyribosomes, and Golgi of fibroblasts, which were the main sites to synthesize proteins, were abundant in the IPL irradiation group, suggesting that these organelles were well prepared for the formation of new collagen. Previous studies have demonstrated a histological increase in collagen types I and III in the dermal extracellular matrix after IPL treatment, 10,17 so this study could explain subcellular structure of the photorejuvenation effects of IPL.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Studies of IPL effects on photoaged skin revealed clinical improvement of wrinkles, pigmentation and telangiectasias [5]. Various hypotheses have been presented to explain the potential mechanisms of IPL effects.…”
Section: Dear Editormentioning
confidence: 98%
“…Since this is an expected occurrence, patients should be appropriately forewarned to prevent unnecessary distress. More prolonged dyschromia, including hypoand hyperpigmentation, may be seen in up to 15% of patients, especially those with darker skin tones, a suntan, or melasma within the treatment area [27]. Such dyschromia usually lasts less than 2 months, and its incidence may be reduced -though likely not entirely eliminated -by following the above-mentioned guidelines regarding various device settings.…”
Section: Intense Pulsed Light Sourcesmentioning
confidence: 99%